Information System of International Conference Management Based on Web - Ahmad Sidiq; Yudianto Sujana; Aris Budianto (Pendidikan Teknik Informatika dan Komputer, Universitas Sebelas Maret, 2018)
Technological advances can be utilized to make information dissemination faster and more efficient. One example of the use of technology as a medium of information and management in the implementation of the conference is an information management system based on WEB. Based on the observations that have been conducted, found various problems, among others for the preparation of activity data reports, data participants, and so forth, actually already utilizing information technology, but still less effective. So many weaknesses that appear like; less effective and efficient in data processing, the time required for the preparation of reports long enough and the risk of error becomes large. Then from the side of presence also still printed manually. In addition, all the participants who register will be placed certificates, although the participants are not present in the conference, this happens because of the organizers difficult to sort out which participants are present and not present. In this article presented the feasibility test results of the conference management information system developed. Testing is performed on system experts, substance experts, and users. Expert testing system using the instrument referring to ISO 9126 get 93% percentage. Expert testing of substance using instrument referring to ISO 9126 get 86% percentage. While testing of users using the instruments that refer to ISO 9126 aspects of functionality gets an average percentage of 88.2%.